ART NOUVEAU HERITAGE AS A RESOURCE IN TOURISM – CHALLENGES AND SOLUTIONS - Rácz, Tamara (Turisztikai és Vidékfejlesztési Tanulmányok, 2022)
This study was carried out in the framework of the ARTNOUVEAU2 international project, and aims to analyse the role of Art Nouveau heritage in tourism. Although Art Nouveau has significant tourist potential in many European cities, the difficulties of collaboration between the cultural sector and the tourism industry create obstacles in its use as a resource in tourism development. Since highlighting Art Nouveau as a major brand component in destination marketing is a crucial step in this process, the paper first provides on overview of the Art Nouveau theme’s appearance in selected European cities’ tourist websites, then discusses the role of tour guides in Art Nouveau tourism and the collaboration possibilities between them and the cultural institutions representing Art Nouveau heritage. Furthermore, the paper also explores the possible contribution of Art Nouveau resources to transforming a destination into a “best place”.